Magnetic and magnetocaloric properties of the La0.9–xAgxMn1.1O3 compounds - Zubov, E.; Pashchenko, A.; Nedelko, N.; Radelytskiy, I.; Dyakonov, K.; Krzyżewski, A.; Ślawska-Waniewska, A.; Dyakonov, V.; Szymczak, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The influence of Ag+ ions and Mn non-stoichiometry on the magnetic properties and magnetocaloric effect in the La0.9–xAgxMn1.1O3 compounds has been studied. The Ag+ ions content substituting for trivalent lanthanum ions was varied from x = 0.05 to 0.3. Magnetic measurements have been performed over a wide temperature (350–5 K) and magnetic field (up to 5 T) ranges. All the manganites studied show the ferromagnetic-like ordering with a first order magnetic phase transition. The magnetic entropy changes were evaluated from the isothermal curves of magnetization versus an applied magnetic field using both the thermodynamic Maxwell relation (MR) and calculation based on the Landau theory of phase transitions. The largest values of the magnetocaloric effect as well as the relative cooling power among the studied manganites are equal to 5.76 J/(kg·K) and 185 J/kg, respectively, for La0.7Ag0.2Mn1.1O3 in the magnetic field change of 5 T near the Curie temperature of TC = 271 K. A good correlation between the magnetization, colossal magnetoresistance and magnetic entropy changes as a function of Ag concentration in the La0.9–xAgxMn1.1O3 manganites was established.